Sex Differences in the Peripheral Immune System in Patients with Depression - Birur, Badari; Amrock, Ellen M.; Shelton, Richard C.; Li, Li (Frontiers in Psychiatry, 2017)
Background: Females are twice as likely as males to experience depression. Recent findings indicate a relationship linking inflammation with depression. Whether the higher prevalence of depression in women is sex-specific or if inflammation contributes to a higher prevalence of depression in females is unclear. Thus, the objective was to determine whether depressed females show higher inflammation compared to males in a cross-sectional study. Materials and Methods: Two-hundred participants were enrolled. Depressive symptoms were assessed using the Montgomery Åsberg Depression Rating Scale (MADRS), and blood samples were collected from all participants to measure inflammatory blood markers. Results: Higher rates of suicidal thoughts, pessimism, and lassitude measured by the MADRS were seen in depressed females compared with depressed males. Among all inflammatory markers measured, there were no significant differences in depressed males vs. male controls. Increased levels of interleukin (IL)-8, interferon-γ and leptin, and decreased levels of IL-5 and adiponectin were observed in depressed females compared to female controls. Compared with depressed males, IL-6 and leptin levels were significantly elevated in depressed females after controlling for body mass index. Correlation analysis revealed that depression severity negatively correlated with IL-12 in males, and positively correlated with IL-1β and tumor necrosis factor (TNF)-α in females. IL-1β and TNF-α correlated with suicidal thoughts, lassitude, and pessimism in depressed females. Conclusion: Our findings indicate a sex-specific relationship between inflammation and depression, which may be important in identifying potential psychopathology and suggesting novel immunomodulatory treatments for depressed females.